2011
DOI: 10.1007/s00426-011-0383-y
|View full text |Cite
|
Sign up to set email alerts
|

Long- and short-term plastic modeling of action prediction abilities in volleyball

Abstract: Athletes show superior abilities not only in executing complex actions, but also in anticipating others' moves. Here, we explored how visual and motor experiences contribute to forge elite action prediction abilities in volleyball players. Both adult athletes and supporters were more accurate than novices in predicting the fate of volleyball floating services by viewing the initial ball trajectory, while only athletes could base their predictions on body kinematics. Importantly, adolescents assigned to physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 124 publications
(184 reference statements)
4
85
0
1
Order By: Relevance
“…Urgesi et al has reported that actual player predict the next movement better than the watching learner in the volleyball learning experiment between two groups: learn by playing and learn by watching others' play [15]. This result also supports our result because we could see the differences between the experienced catcher and the unexperienced catcher in our present experiment results.…”
Section: Discussionsupporting
confidence: 90%
“…Urgesi et al has reported that actual player predict the next movement better than the watching learner in the volleyball learning experiment between two groups: learn by playing and learn by watching others' play [15]. This result also supports our result because we could see the differences between the experienced catcher and the unexperienced catcher in our present experiment results.…”
Section: Discussionsupporting
confidence: 90%
“…While prior literature has shown that perceptual experience alone can impact how we perceive or predict others' actions (e.g., Buchanan & Wright, 2011;Cross et al, 2009Cross et al, , 2011Higuchi, Holle, Roberts, Eickhoff, & Vogt et al, 2012), a number of significant unexplored questions remain regarding the role of physical compared to visual expertise. Here, Urgesi, Savonitto, Fabbro, & Aglioti (2011) demonstrate that adult volleyball players and spectators are more accurate than novices in predicting volleyball serves, but only the players were able to base their predictions on kinematic information. To more fully understand the mechanism behind this finding, Urgesi et al ran a follow up experiment where adolescent volleyball players were taught a new serve either by physical or observational practice.…”
mentioning
confidence: 72%
“…As their greater action simulation abilities could have biased the results, individuals with any motor expertise in playing soccer were excluded from the experiment by means of a pre-screening procedure. Athletes, in fact, present superior abilities in predicting and anticipating other players' actions Aglioti et al, 2008;Makris & Urgesi, 2014;Sebanz & Shiffrar, 2009;Tomeo, Cesari, Aglioti, & Urgesi, 2012;Urgesi et al, 2012;Weissensteiner et al, 2008). Notably, also observational practice may contribute to action prediction abilities (Urgesi, Savonitto, Fabbro, & Aglioti, 2012), and soccer is a quite familiar sport.…”
Section: Participantsmentioning
confidence: 99%